Association Between the Methylation Statuses at CpG Sites in the Promoter Region of the SLCO1B3, RNA Expression and Color Change in Blue Eggshells in Lushi Chickens - Zhuanjian Li; Zhuanjian Li; Tuanhui Ren; Wenya Li; Yu Zhou; Ruili Han; Ruili Han; Hong Li; Hong Li; Ruirui Jiang; Ruirui Jiang; Fengbin Yan; et al. (Frontiers in Genetics, 2019)
The formation mechanism underlying the blue eggshell characteristic has been discovered in birds, and SLCO1B3 is the key gene that regulates the blue eggshell color. Insertion of an endogenous retrovirus, EAV-HP, in the SLCO1B3 5′ flanking region promotes SLCO1B3 expression in the chicken shell gland, and this expression causes bile salts to enter the shell gland, where biliverdin is secreted into the eggshell, forming a blue shell. However, at different laying stages of the same group of chickens, the color of the eggshell can vary widely, and the molecular mechanism underlying the eggshell color change remains unknown. Therefore, to reveal the molecular mechanism of the blue eggshell color variations, we analyzed the change in the eggshell color during the laying period. The results indicated that the eggshell color in Lushi chickens can be divided into three stages: 20–25 weeks for dark blue, 26–45 weeks for medium blue, and 46–60 weeks for light blue. We further investigated the expression and methylation levels of the SLCO1B3 gene at eight different weeks, finding that the relative expression of SLCO1B3 was significantly higher at 25 and 30 weeks than at other laying weeks. Furthermore, the overall methylation rate of the SLCO1B3 gene in Lushi chickens increased gradually with increasing weeks of egg production, as shown by bisulfite sequencing PCR. Pearson correlation analysis showed that methylation of the promoter region of SLCO1B3 was significantly negatively correlated with both SLCO1B3 expression in the shell gland tissue and eggshell color. In addition, we predicted that CpG5 and CpG8 may be key sites for regulating SLCO1B3 gene transcription. Our findings show that as the level of methylation increases, methylation of the CpG5 and CpG8 sites hinders the binding of transcription factors to the promoter, reducing SLCO1B3 expression during the late period and resulting in a lighter eggshell color.